Gray-Scale Image Brightness/Contrast Enhancement with Multi-Model Histogram linear Contrast Stretching (MMHLCS) method - Al-Hamadi, Faisel G.M. (Iraqi Journal of Physics, 2009)
Gray-Scale Image Brightness/Contrast Enhancement with Multi-ModelHistogram linear Contrast Stretching (MMHLCS) method